Antibacterial Activity of Mixed Infusion of Averrhoa bilimbi L. Fruit and Cananga odorata Flowers Against Several Numbers of Bacterial Colonies in Vitro Test - Lia Yulia Budiarti; Siti Kaidah; Nur Adnia; Vania Puspitasari Sangadi (Fakultas Kedokteran Universitas Lambung Mangkurat, 2023)
Abstract: Antiseptic alcohol 70% is known to be effective in inhibiting the growth of bacterial colonization on the hands, but its use in the long term can cause skin disorders. An alternative antiseptic can be made from a mixture of star fruit (Averrhoa bilimbi L.) and flower Cananga (Cananga odorata) which contains several antibacterial compounds. The purpose of this study was to analyze the antibacterial activity of the infusion mixture of Averrhoa bilimbi and Cananga odorata flowers in inhibiting the growth of Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, Salmonella typhi, and Shigella sonnei bacteria. This in vitro research design used a posttest only with control group design with the observation parameter being the number of test bacteria colonies that grew on the observation medium. The treatments tested were a mixture of 50%, 75%, and 100% Averrhoa bilimbi infusion and 100% Cananga odorata, and 70% alcohol control. The results showed that the infusion mixture of Averrhoa bilimbi and Cananga odorata had different inhibitory effects on Gram-positive and Gram-negative bacteria; the number of colonies of Staphylococcus aureus, Staphylococcus epidermidis, and Escherichia coli was not significantly different from the mixed treatment concentration of 100% (1:1) with 70% alcohol treatment. In conclusion, the infusion mixture of Averrhoa bilimbi fruit and Cananga odorata flower had antibacterial activity against Gram-positive and Gram-negative bacteria, and the best inhibitory effect was obtained in the 100% infusion mixture treatment.